EXPERIENTIAL LEARNING: INCLUSIVE ART EDUCATION FOR JOYFUL LEARNING - Thote, Prashant; Kumar Sen, Rajesh (International Journal of Research -GRANTHAALAYAH, 2019)
Art integrated learning makes class-room transition joyful, creative and promote appreciation of our rich and cultural heritage. It also promotes art based enquiry, investigation, exploration critical thinking and creativity for class, conceptual understanding of the concepts among the students.It also enhances experiential learning, as it enables students to drive meaning and understanding.Despite the challenging situation facing art education in schools but there are some exemptions.This paper is based on the ethnographic case study of the school to explore art education.In this school art is integrated as natural part of school thathas taken holistic approach to education.Art education practices were carried out in creative manner.